Effects of Arctium lappa aqueous extract on lipid profile and hepatic enzyme levels of sucrose-induced metabolic syndrome in female rats (Brazilian Journal of Pharmaceutical Sciences, 2016)
Arctium lappa is known to have antioxidant and antidiabetic effects in traditional medicine. Objectives: The aim of this paper was to study the effects of A. lappa root extract (AE) on lipid profile and hepatic enzyme levels in sucrose-induced metabolic syndrome (MS) in female rats. The study used 40 adult female Wistar rats weighing 150 g-250 g randomly divided into five groups: control, metabolic syndrome (MS), metabolic syndrome+AE at 50,100, 200 mg/kg. MS was induced by administering 50% sucrose in drinking water for 6 weeks. AE was intra-peritoneally administered daily at doses of 50,100, and 200 mg/kg for two sequential weeks at the end of the fourth week in metabolic syndrome rats. Twenty-four hours after the last administration of AE, blood was collected and centrifuged, and then the serum was used for the measurement of lipid profile and hepatic enzyme. Serum glucose, insulin, fasting insulin resistance index, body weight, water intake, lipid profile, and hepatic enzymes were significantly increased although food intake was decreased in MS rats compared to the control rats. The lipids and liver enzymes were reduced by AE extracts in the MS group. This study showed that the A. lappa root aqueous extract exhibits a hypolipidemic activity of hyperlipidemic rats. This activity is practically that of a triple-impact antioxidant, hypolipidemic, and hepatoprotective.